Influences of 27-Gauge Vitrectomy on Corneal Topographic Conditions - Takafumi Hirashima; Takao Utsumi; Miou Hirose; Hideyasu Oh (Journal of Ophthalmology)
Purpose. To evaluate the influences of 27-gauge vitrectomy on corneal topographic conditions. Method. Fifty-six eyes of 56 patients undergoing 27-gauge vitrectomy were retrospectively studied. Twenty-three eyes with epiretinal membrane (ERM), 23 eyes with macular hole (MH), and 10 eyes with proliferative diabetic retinopathy (PDR) were included. Forty-five of the 56 eyes underwent 27-gauge phacovitrectomy (group 1), and the remaining 11 eyes underwent 27-gauge vitrectomy alone (group 2). Corneal topography was obtained with a wave-front analyzer preoperatively and at 1 and 3 months postoperatively. The corneal topographic parameters evaluated were the average corneal power, regular astigmatism, spherical aberration, and higher-order aberration (HOA). Results. In between-group analyses of groups 1 and 2, no significant differences were observed regarding the changes of the 4 parameters from the baseline to 1 and 3 months postoperatively. No significant differences in the changes of all parameters from the baseline to 1 and 3 months postoperatively were also observed between MH group and the other two groups. A significant difference in the change of HOA from the baseline to 1 month postoperatively was observed between ERM and PDR group however, the difference disappeared at 3 months. Conclusion. 27-gauge vitrectomy did not induce substantial changes in the corneal topographic conditions.